The National Research Council of Canada: Its Historiography, its Chronology, its Bibliography - Phillipson, Donald (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1991)
AbstractThe history of the NRC is approached from two perspectives: first, in terms of the historiographical ideas presented in the literature, and second, in terms of its place within the science policy debates. There follow a select chronology and bibliography of the NRC.